The Adventures of Harry Revel - Quiller-Couch, Arthur, 1863-1944 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Adventures of Harry Revel" by Arthur Quiller-Couch is a novel written in the early 20th century. The story follows the life and early experiences of Harry Revel, a foundling raised in the Genevan Hospital in Plymouth. The narrative begins with his childhood observations and relationships, particularly with the matron Miss Plinlimmon, as he navigates the trials of growing up in a unique setting. At the start of the book, Harry Revel vividly describes his life as a foundling in the Genevan Hospital. He recalls the strict rules and daily routines governed by the pastor and the matron, as well as the camaraderie among the other boys. The narrative captures his youthful innocence amidst the backdrop of a larger world that seems both enticing and unsettling. Revel's vivid memories include a mix of playful adventures and darker realizations, hinting at the complexities of his identity and future. The opening sets the stage for Harry's journey as he faces the challenges of his circumstances, introducing readers to the whimsical yet harsh realities of his world. (This is an automatically generated summary.)
Release date is 2007-01-03
E-text prepared by Lionel Sear
Keywords: England -- Social life and customs -- 19th century -- Fiction; Humorous stories; Foundlings -- Fiction; Boys -- Fiction; Adventure stories